Acute disseminated encephalomyelitis due to abrus precatorius poisoning - A case report - Elizabeth C. Ninan; Emmanuel James (Elsevier, 2019)
Abrus precatorius, commonly known as 'Rosary pea' or 'Jequirity pea' and known as 'Shisham, Batrah-Hindi or Ain Alfreeth' in the Middle East, grows wild in the tropical and subtropical areas of the world. The seeds of the plant contain one of the most potent toxins known to man. Poisoning with abrus seeds is a rare occurrence as the harder outer coat of the seeds generally resists digestion and such reports are scarce in the literature. We present here a case of a 22 year old lady who developed severe vomiting, diarrhoea and malena at the initial stages and later seizures and acute disseminated encephalomyelitis due to deliberate chewing and swallowing of abrus seeds. She was rescued with several sessions of membrane plasmapheresis and supportive care. The neuropathological process of acute disseminated encephalomyelitis due to abrus poisoning was reversed by plasmapheresis. Keywords: Abrus precatorius, Abrin, Acute disseminated encephalomyelitis, Corticosteroids, Plasmapheresis